Simplified Granger causality map for data-driven root cause diagnosis of process disturbances. (November 2020) - Liu, Yi; Chen, Han-Sheng; Wu, Haibin; Dai, Yun; Yao, Yuan; Yan, Zhengbing
Abstract: Root cause diagnosis is an important step in process monitoring, which aims to identify the sources of process disturbances. The primary challenge is that process disturbances propagate between different operating units because of the flow of material and information. Data-driven causality analysis techniques, such as Granger causality (GC) test, have been widely adopted to construct process causal maps for root cause diagnosis. However, the generated causal map is over-complicated and difficult to interpret because of the existence of process loops and the violation of statistical assumptions. In this work, a two-step procedure is proposed to solve this problem. First, a causal map is built by adopting the conditional GC analysis, which is viewed as a graph in the next step. In this graph, each vertex corresponds to a process variable under investigation, while the weight of the edge connecting two vertices is the F-value calculated by conditional GC. This graph is then simplified by computing its maximum spanning tree. Thus, the results of the causality analysis are transformed into a directed acyclic graph, which eliminates all loops, highlights the root cause variable, and facilitates the diagnosis. The feasibility of this method is illustrated with the application to the Tennessee Eastman benchmark process. In the investigated case studies, the proposed method outperforms the conditional GC test and provides an easy way to identify the root cause of process disturbances. Highlights: A simplified Granger causality map is proposed for root cause diagnosis. The Granger causality map is simplified by finding its maximum spanning tree. The problems caused by redundant candidate variables and process loops are solved. The root cause is highlighted in the simplified causal map.